Subduction zone fluids and arc magmas conducted by lithospheric deformed regions beneath the central Andes - E. Contreras-Reyes (Nature Portfolio, 2021)
Abstract Dehydration of the oceanic subducting slab promotes the formation of magmatic arcs, intra-slab intermediate-depth seismicity, and hydration of the overlying mantle wedge. However, the complex permeability structure of the overriding plate controls the magma and fluid migration and their accumulation at shallower depths. In this regard, mapping the inner structure of the overriding crust and mantle is crucial to understand the magmatic and hydrological processes in subduction zones. We integrate 3-D P-wave, $$V_p/V_s$$ V p / V s , and electrical resistivity tomographic models of the northern Chilean subduction zone to map the magmatic and fluids derived from the subducting oceanic Nazca plate. Results show a continental crust relatively thick (50–65 km) characterized by a lower zone of high $$V_p$$ V p values (7.2–7.6 km/s), which is interpreted as the presence of plutonic rocks. The mantle lithospheric wedge is weakly hydrated ( $$V_p/V_s$$ V p / V s = 1.75–1.8) while the forearc continental crust is traversed by regions of reduced electrical resistivity values ( $$< 10^2$$ < 10 2 $$Ω m$$ Ω m ) interpreted as zones of relatively high permeability/fracturing and fluid content. These regions spatially correlate with upper plate trans-lithospheric deformation zones. Ascending melts accumulate preferentially in the back-arc, whereas hydrothermal systems form trenchward of the volcanic arc. The results highlight the complex permeability structure of the upper South American plate.